PDF ANALISIS STRUKTUR DAN KAIDAH KEBAHASAAN TEKS EKSPLANASI PADA PESERTA DIDIK KELAS XI MA MIFTAHUL ULUM ATTOHIRIN GONDANGLEGI MALANG TAHUN 2019/2020 - Yusron Yusuf; Devi (Jurnal Tinta, 2020)
In the explanatory text it has a plot or structure like other types of text, such as general statements, cause and effect and interpretation. The explanatory text also has linguistic rules which include copula, active verbs, conjunctions, adverbs of time, scientific terms, pronouns. This research is entitled "Analysis of the Structure and Rules of Explanatory Text in Class XI Students MA Miftahul Ulum Attohirin Academic Year 2019/2020. To find out the problems in conjunction analysis in a collection of explanatory texts in class XI MA Miftahul Ulum Attohirin students, it is necessary to formulate the problem as well as the formulation of the problem, namely, 1) What is the structure of the explanatory text in class XI MA Miftahul Ulum Attohirin Gondanglegi Malang students? 2) What are the rules of language explanation text in class XI MA Miftahul Ulum Attohirin Gondanglegi Malang?. This type of research is a descriptive qualitative research type. The qualitative research method is a research method based on the philosophy of postpositivism, this method is used to study natural objects. Where the researcher is the key instrument, the data collection technique is done by triangulation or a combination, the data analysis is inductive/qualitative and the results of qualitative research emphasize the meaning rather than generalization. Based on the data analysis carried out, it was concluded that 8 students were able to determine the structure of the expansion text well. Learners are able to determine the structure of general statements, cause and effect, and interpretation. In the explanatory text linguistic rules, there are 6 out of 11 students who are able to determine the rules of the explanatory text language. Students do not understand the language rules of explanatory text such as copula, conjunction, active verbs, adverbs of time, scientific terms and noun pronouns.